Trade, Finance, Specialization, and Synchronization - Imbs, Jean (IMF Working Papers; Working Paper ;, 2003)
The paper investigates the determinants of business cycles synchronization across regions. It uses both international and intranational data to evaluate the linkages between trade in goods, trade in financial assets, specialization and business cycles synchronization using a system of simultaneous equations. The results are as follows: (i) Simultaneity is important, as both trade and financial openness have a direct and an indirect effect on cycle synchronization. (ii) A variety of alternative measures of financial integration suggest that regions with strong financial links are significantly more synchronized, though they are also more specialized. (iii) Specialization patterns have a sizable effect on business cycles, beyond their reflection of intra-industry trade, and of openness to goods and assets trade. (iv) The estimated role of trade is in line with existing models once intra-industry trade is controlled for. The results relate to a recent strand of international business cycle models with incomplete markets and transport costs, and, on the empirical side, point to an important omission in the usual criteria defining an optimal currency area, namely specialization patterns.